The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1108/ils-08-2019-0081
|View full text |Cite
|
Sign up to set email alerts
|

The impact of different play activity designs on students’ embodied learning

Abstract: Purpose This paper aims to build on work that has demonstrated the value of play or game-based learning environments and to further unpack how different kinds of play activities can support learning of academic concepts. To do so, this paper explores how students learn complex science concepts through collective embodied play by comparing two forms of play labeled as Inquiry Play and Game Play. Design/methodology/approach This study builds off of previous research that uses the Science Through Technology Enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…A common theme in the studies above is that the digital tools provide young learners with affordances to visualize and actively manipulate simulations and explore changes in particle behavior that result. Further, the research of Davis et al (2019) suggests that teacher discourse orienting children to science content during inquiry play with a digital tool is important to learning. This research supports our conjecture that young children can learn particle models of matter with the appropriate social and material supports.…”
Section: Why We Chose Mattermentioning
confidence: 99%
See 1 more Smart Citation
“…A common theme in the studies above is that the digital tools provide young learners with affordances to visualize and actively manipulate simulations and explore changes in particle behavior that result. Further, the research of Davis et al (2019) suggests that teacher discourse orienting children to science content during inquiry play with a digital tool is important to learning. This research supports our conjecture that young children can learn particle models of matter with the appropriate social and material supports.…”
Section: Why We Chose Mattermentioning
confidence: 99%
“…Their qualitative study showed that children aged 11–14 years could productively construct and revise particle models through gameplay. Using embodied cognition frameworks, researchers have designed augmented reality‐based collaborative learning activities to help first‐ and second‐grade children model the particle behavior of water in different physical states (Danish et al, 2020; Davis et al, 2019; DeLiema et al, 2019). Jakab (2013) found that 6‐year‐olds who engaged in didactic interviews with an adult around a web‐based interactive game (the Molecularium) for modeling particle behavior could construct productive ideas of molecules.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…And what value do different games and forms of play have for supporting learning? While Williams-Pierce (2019) compares and contrasts the affordances of games, simulations, and tutors, and how they support mathematical play, Davis et al (2019) dive deeper into the forms of play afforded by different game contexts. They make the keen observation that existing research on play, games, and learning often "treats all games as having the same properties, or all play as having the same value".…”
Section: Articles In This Special Issuementioning
confidence: 99%